ANALISIS IMPLEMENTASI TRANSFER PRICING ANTAR PERUSAHAAN YANG MEMILIKI HUBUNGAN ISTIMEWA DI BATAM DAN SINGAPURA - Teza, Serli Diovani; Ningsih, Desrini (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
The purpose of this study is to analyze and describe the implementation of intercompany transfer pricing policies related in Batam and Singapore. This research uses descriptive and qualitative methods. As we know Batam is an industrial city that average people work as laborers in the Company. Batam is located 20 kilometers from Singapore, which has one of the busiest ports in the world. Batam is an industrial area that is growing rapidly and has a strategic location on the trade route Malacca Strait, in neighboring Singapore and Malaysia. Its strategic location allows Batam become a leading industry in the island country. Located in the path beside the busy trading, Batam also has a lot of big and small islands that become economic assets in line with the economic development and the impact comes the practice of transfer pricing. Transfrer pricing this is a serious problem for the country because it directly affects the amount of aggregate income countries. Although the general tax directorate has arranged all related to transfer pricing but the implementation has not gone well in accordance with the government policy for the average companies tend to pursue lower taxes. Taxes in Singapore by 17% lower compared to the tax in Indonesia is 25%.